The answer is b.
Because you multiply (5•12)
Answer:
-2x
Step-by-step explanation:
4x-6x=-2x. You need to combine like terms or subtract 6 from 4 which is -2 the you add then put the x back in
Answer:
We are given a equation as:
5log(x+3)=5
We are asked to find a graph that is used to solve the above equation.
We can write the given equation as:
we will divide both side of the equation by 5 to obtain:
log(x+3)=1
Now we have to determine which graph represents the function:
y=log(x+3)
since we know that when x=-2.
y=log(-2+3)=log(1)=0
Hence, the graph should pass through (-2,0).
Hence, the graph that satisfies this is attached to the answer.
Step-by-step explanation:
Answer:
Explained below.
Step-by-step explanation:
Convenience sampling is a kind of non-probability-sampling (i.e. all items doesn’t have an equivalent chance of being selected), which doesn’t comprises of random collection of items.
Convenience sampling is where we take in items which are easy to reach. This sort of sampling technique results in a biased sample.
Systematic sampling is a kind of probability sampling method in which individuals from a larger population are nominated according to a random initial point and a static, periodic interval. If the individual <em>k</em> is selected as the first sample then the sample space consists of every <em>k</em>th individual.
In this case the first sample is an example of convenience sample and the second is a systematic sample.
Answer:
Remember,
and the range of g must be in the domain of f.
a)
![f(g(x))=f(x-1)=(x-1)^2-(x-1)=x^2-2x+1-x+1=x^2-3x+2](https://tex.z-dn.net/?f=f%28g%28x%29%29%3Df%28x-1%29%3D%28x-1%29%5E2-%28x-1%29%3Dx%5E2-2x%2B1-x%2B1%3Dx%5E2-3x%2B2)
![g(f(x))=g(x^2-x)=(x^2-x)-1=x^2-x-1](https://tex.z-dn.net/?f=g%28f%28x%29%29%3Dg%28x%5E2-x%29%3D%28x%5E2-x%29-1%3Dx%5E2-x-1)
The domain of f(g(x)) and g(f(x)) is the set of reals.
b)
![f(g(x))=f(\sqrt{x}-2)=(\sqrt{x}-2)^2-x=\sqrt{x}^2-2*2*\sqrt{x}+2^2-x=-4\sqrt{x}+4](https://tex.z-dn.net/?f=f%28g%28x%29%29%3Df%28%5Csqrt%7Bx%7D-2%29%3D%28%5Csqrt%7Bx%7D-2%29%5E2-x%3D%5Csqrt%7Bx%7D%5E2-2%2A2%2A%5Csqrt%7Bx%7D%2B2%5E2-x%3D-4%5Csqrt%7Bx%7D%2B4)
![g(f(x))=g(x^2-x)=\sqrt{x^2-x}-2](https://tex.z-dn.net/?f=g%28f%28x%29%29%3Dg%28x%5E2-x%29%3D%5Csqrt%7Bx%5E2-x%7D-2)
The domain of f(g(x)) is the set of nonnegative reals and the domain of g(f(x)) is the set of number such that ![x^2-x\geq 0](https://tex.z-dn.net/?f=x%5E2-x%5Cgeq%200)
c)
![f(g(x))=f(\frac{1}{x-1})=(\frac{1}{x-1})^2=\frac{1}{(x-1)^2}](https://tex.z-dn.net/?f=f%28g%28x%29%29%3Df%28%5Cfrac%7B1%7D%7Bx-1%7D%29%3D%28%5Cfrac%7B1%7D%7Bx-1%7D%29%5E2%3D%5Cfrac%7B1%7D%7B%28x-1%29%5E2%7D)
![g(f(x))=g(x^2)=\frac{1}{x^2-1}](https://tex.z-dn.net/?f=g%28f%28x%29%29%3Dg%28x%5E2%29%3D%5Cfrac%7B1%7D%7Bx%5E2-1%7D)
The domain of f(g(x)) is the set of reals except the 1 and the domain of g(f(x)) is the set of reals except the 1 and -1
d)
![f(g(x))=f(\frac{1}{x-1})=\frac{1}{(\frac{1}{x-1}-1)}=\frac{1}{\frac{2-x}{x-1}}=\frac{x-1}{2-x}](https://tex.z-dn.net/?f=f%28g%28x%29%29%3Df%28%5Cfrac%7B1%7D%7Bx-1%7D%29%3D%5Cfrac%7B1%7D%7B%28%5Cfrac%7B1%7D%7Bx-1%7D-1%29%7D%3D%5Cfrac%7B1%7D%7B%5Cfrac%7B2-x%7D%7Bx-1%7D%7D%3D%5Cfrac%7Bx-1%7D%7B2-x%7D)
![g(f(x))=g(\frac{1}{x+2})=\frac{1}{(\frac{1}{x+2}-1)}=\frac{1}{\frac{-x-1}{x+2}}=\frac{x+2}{-x-1}](https://tex.z-dn.net/?f=g%28f%28x%29%29%3Dg%28%5Cfrac%7B1%7D%7Bx%2B2%7D%29%3D%5Cfrac%7B1%7D%7B%28%5Cfrac%7B1%7D%7Bx%2B2%7D-1%29%7D%3D%5Cfrac%7B1%7D%7B%5Cfrac%7B-x-1%7D%7Bx%2B2%7D%7D%3D%5Cfrac%7Bx%2B2%7D%7B-x-1%7D)
The domain of f(g(x)) is the set of reals except 2, and the domain of g(f(x)) is the set of reals except -1.
e)
![f(g(x))=f(log(2(x+3)))=f(log(2x+6))=log(2x+6)-1](https://tex.z-dn.net/?f=f%28g%28x%29%29%3Df%28log%282%28x%2B3%29%29%29%3Df%28log%282x%2B6%29%29%3Dlog%282x%2B6%29-1)
![g(f(x))=g(x-1)=log(2(x-1)+6)=log(2x+4)](https://tex.z-dn.net/?f=g%28f%28x%29%29%3Dg%28x-1%29%3Dlog%282%28x-1%29%2B6%29%3Dlog%282x%2B4%29)
The domain of f(g(x)) is the set of nonnegative reals except -3. The domain of g(f(x)) is the set of nonnegative reals except -2.